1987
DOI: 10.1021/np50051a037
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids of Cotula cinerea

Abstract: Cotula L. (Compositae), the largest genus in the tribe Anthemideae (I), is a widespread Southern hemisphere group of about 80 species. The Anthemideae was arranged by Reitbrecht (2) into seven provisional subtribal groups and follows the original scheme of Bentham (3). Cotula and its relatives are placed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
(4 reference statements)
3
13
0
Order By: Relevance
“…Thus compound 11 showed peaks at m/z 463 and 301 corresponding to the [M − H] − ion and the subsequent loss of a hexose moiety [M − H − 162] − . This compound was thus concluded to be quercetin 3‐ O ‐glucoside as has been already described in Cotula cinerea extracts . The presence of the quercetin aglycone peak corresponding to the Y 0 − ion at m/z 301 and subsequent product ions at m/z 257, 179, and 151, consistent with the quercetin aglycone, were also observed for the compounds.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Thus compound 11 showed peaks at m/z 463 and 301 corresponding to the [M − H] − ion and the subsequent loss of a hexose moiety [M − H − 162] − . This compound was thus concluded to be quercetin 3‐ O ‐glucoside as has been already described in Cotula cinerea extracts . The presence of the quercetin aglycone peak corresponding to the Y 0 − ion at m/z 301 and subsequent product ions at m/z 257, 179, and 151, consistent with the quercetin aglycone, were also observed for the compounds.…”
Section: Resultssupporting
confidence: 71%
“…All these compounds have been previously reported, and their structures were also confirmed using the single ion monitoring acquisition mode which allowed the molecular formulae of the corresponding compounds to be obtained.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The MeOH extracts were subjected to Diaion HP-20 column chromatography to give H 2 O-and MeOH-eluted fractions, respectively. The MeOH-eluted fraction from P. suffruticosa flowers was subjected to silica gel and ODS column chromatography and finally HPLC to furnish a new monoterpene glycoside, floralalbiflorin I (1, 0.00224%, the yield isolated from P. suffruticosa flowers), together with 21 known compounds, methyl gallate (3, 0.31%) (Ma et al, 2005), gallic acid (4, 0.0017%) (Wei et al, 2005), 1-O-(4-hydroxybenzoyl)-b-D-galactopyranoside (5, 0.00098%) (Kiso et al, 2000), 2-phenylethyl-b-D-glucopyranoside (7, 0.0037%) (Shu and Lawrence, 1994), salidroside (8, 0.00057%) , 4-hydroxyphenylethyl-b-D-galactopyranoside (9, 0.00059%) (Guo et al, 2010), 1,2,3,4,6-penta-O-galloyl-b-D-glucopyranoside (10, 0.19%) (Nishizawa et al, 1982), apigenin (11, 0.00021%) (Markham et al, 1978), apigenin 7-O-b-D-glucopyranoside (12, 0.0011%) (Redaelli et al, 1980), luteolin (13, 0.0013%) (Park et al, 2007), luteolin 7-O-b-D-glucopyranoside (14, 0.0018%) (Ahmed et al, 1987), kaempferol (15, 0.00040%) (Okuyama et al, 1978), kaempferol 3-O-b-D-glucopyranoside (16, 0.00015%) (Markham et al, 1978), kaempferol 7-O-b-D-glucopyranoside (17, 0.0019%) (Markham et al, 1978), quercetin 3-O-b-D-glucopyranoside (18, 0.00023%) (Markham et al, 1978), chalcononaringenin 4-O-b-Dglucopyranoside (25, 0.0016%) (Iwashina et al, 2005), paeoniflorin (26, 0.064%) (Lin et al, 1996), oxypaeoniflorin (27, 0.0014%) (Kaneda et al, 1972), mudanpioside I (28, 0.00037%), benzoylpaeoniflorin (29, 0.00052%) (Ding et al, 1999), and sachaloside (30, 0.00075%) (Cheng et al, 2010). The MeOH-eluted fraction from P. lactiflora flowers was also subjected to silica gel and ODS column chromatography and finally HPLC to furnish a new flavonol glycoside, lactifloraoside I (2, 0.0068%, the yield isolated from P. lactiflora flowers), together with 13 known compounds, 3 (0.038%), methylarbutin (6, 0.00071%) (Quintus et al, 2005), 10 (1.27%) (Nishizawa et al, 1982), 16 (0.0034%) (Markham et al, 1978), 18 (0.0027%) (Markham et al, 1978), kaempferol 3,7-O-b-D-diglucopyranoside (19, 0.0011%) (Markham et al, 1978), kaempherol 3-O-...…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al (1987) investigated the flavonoids of Cotula cinerea and found that the aerial parts of the plant contain kaempferitin, quercetrin, quercetin, kaempferol and some other flavonoid compounds.…”
mentioning
confidence: 99%